Pengaruh pemberian reward dan ice breaking terhadap minat belajar matematika - A'ini, Wahyu Nur; Riyadi, Riyadi; Budiharto, Tri (Universitas Sebelas Maret, 2023)
This study aims to examine the impact of rewards and ice breaking activities on the level of interest in learning mathematics among fifth-grade students in Laweyan, Surakarta. The research use quantitative method, specifically utilizing a quasi-experimental with nonequivalent control group design. Data for the study were gathered together through a pretest and posttest questionnaire to measure students’interest in learning mathematics. The sampling technique employed was cluster random sampling, ensuring that the sample is both effective and representative. The findings indicate that experimental group show a higher level of interest in learning compared to those in the control group. The hypothesis test results, with an Asymp. Sig value of , reject the null hypothesis () and confirm a significant impact of the intervention (), involving rewards and ice breaking, on interest in learning mathematics (). The test outcomes provide evidence of positive impact of offering rewards and engaging in ice breaking activities on the interest in learning mathematics among fifth-grade students.